Evaluation of development of clinical reasoning skills in dental students through diagnostic thinking inventory - Ahmed, Sanaa; Shah, Hina; Raza, Syeda Zarreen (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the clinical reasoning skills among dental students, and to compare the diagnostic thinking ability of male and female students. Method: The cross-sectional study was conducted from May to July 2021 at a public-sector dental school in Karachi, and comprised students of both genders from across all the four years of dental school. Data was collected using the diagnostic thinking inventory which also assessed flexibility in thinking and knowledge structure in memory. Data was analysed using SPSS 18. Results: Of the 111 forms distributed, 108(98.2%) were received duly filled; 32(29.35%) from male students and 76(69.72) from female students. Participants from the first year were 24(22%), second year 23(21%), third year 33(30.27%) and the fourth year 29(26.6%). The reliability of diagnostic thinking inventory was 0.906, for knowledge structure in memory 0.661, and flexibility in thinking 0.573. The correlation was significant for students in their 2nd, 3rd and 4th years of studies (p=0.01) The overall mean score was <150 which was poor. Both the knowledge structure in memory, and flexibility in thinking scores were higher for females compared to males (Significant at the level of 0.01). Conclusion: The clinical reasoning skills of students were low, and the diagnostic thinking ability of female students was better than that of their male counterparts. Key Words: Students, Dental Schools, Dental, Problem-based Learning, Clinical Competence, Clinical reasoning.